(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: To evaluate early results of percutaneous coronary intervention in patients with ST-segment elevation acute myocardial infarction (STEMI). Method: Cross-sectional description. Total 106 participating patients diagnosed with ST-segment elevation acute MI received percutaneous coronary intervention at Nghe An General friendship Hospital from January 2020 to December 2020. Results: Mean age was 71.67±13.13 years old. The majority of patients were > 60 years old, accounting for 78.3%. The rate of male is 72.6% higher than that of female is 27.4%. The proportion of patients who received intervention by radial artery, accounted for 87.7%. The rate of patients having stent placement after balloon angioplasty was 86.8%. The average time of the ball door was 96.7±38.22 minutes, of which 65 patients reached the time of the balloon door <90 minutes. The success rate of the procedure is 94.3% and 90.2% of patients after the intervention have a clinical success rate. The mortality rate after the intervention is 5.6%. Conclusion: Prompt primary percutaneous coronary intervention for acute STEMI is feasible in our setup and is associated with high success rate, low mortality rates and low complication rates